Melancholic Mem in the Third Life of Grange Copeland - Sedehi, Kamelia Talebian; Talif, Rosli; Wan Yahya, Wan Roselezam; Jujar Singh, Hardev Kaur (Universiti Putra Malaysia Press, 2015)
Julia Kristeva's notion of the melancholic subject deals with the subject's sense of loss in the absence of the unnameable Thing. As a result of melancholia, the melancholic subject is a stranger to his mother tongue and cannot express his feelings through language; therefore, he cannot communicate with others. Using this framework, this article focuses on Alice Walker's The Third Life of Grange Copeland in light of Julia Kristeva's melancholic subject. In this novel, Mem is tormented, both physically and psychologically, by her husband. As a result of her loss of a mother figure and husband's affection, she falls into melancholia. This article sheds light on how Mem's loss of a mother figure and lack of love from her husband leads her to melancholia and how she reacts to the physical and psychological pressures she must confront.